2022
DOI: 10.1177/00332941221077909
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the General and Specific Domains of Self-Esteem: The Short-form of the State Self-Esteem Scale

Abstract: Self-esteem is a crucial human nature feature for understanding the social dimensions of individuals’ self-concept. One of its characteristics is peoples’ malleability to adapt to social contexts, that is, the state self-esteem (SSE). Individuals express SES in three different factors: performance; social success; and physical appearance. Along with three studies, we present evidence of validity of the Short-Form of State Self-Esteem Scale (SSES-S) that measures contextual fluctuations in individuals’ self-est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…High scores indicate high-state self-esteem, while low scores indicate low-state self-esteem. Brito et al [55] conducted convergent and discriminant validities of the SSES and found it to show a strong, positive, and significant correlation with the Rosenberg self-esteem scale. The internal reliability for performance is .77, social is .72, and appearance is .83.…”
Section: State Self-esteem Scale (Sses)mentioning
confidence: 99%
“…High scores indicate high-state self-esteem, while low scores indicate low-state self-esteem. Brito et al [55] conducted convergent and discriminant validities of the SSES and found it to show a strong, positive, and significant correlation with the Rosenberg self-esteem scale. The internal reliability for performance is .77, social is .72, and appearance is .83.…”
Section: State Self-esteem Scale (Sses)mentioning
confidence: 99%